2013
DOI: 10.1016/j.ejphar.2012.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological examination of trifluoromethyl ring-substituted methcathinone analogs

Abstract: Cathinones are a class of drugs used to treat various medical conditions including depression, obesity, substance abuse, and muscle spasms. Some “designer” cathinones, such as methcathinone, mephedrone, and methylone, are used nonclinically for their stimulant or entactogenic properties. Given the recent rise in nonmedical use of designer cathinones, we aimed to improve understanding of cathinone pharmacology by investigating analogs of methcathinone with a CF3 substituent at the 2-, 3-, or 4-position of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 33 publications
9
69
0
Order By: Relevance
“…These results are consistent with previous microdialysis studies in both rats (Baumann et al, 2000;Kehr et al, 2011) and nonhuman primates (Laruelle et al, 1997;Murnane et al, 2010;Sawyer et al, 2012), and confirm the sensitivity of this microdialysis procedure to changes in NAc DA and 5-HT levels produced by agents that have been extensively evaluated. Also consistent with a previous MCAT microdialysis study (Cozzi et al, 2013), MCAT displayed a greater potency to increase NAc DA versus 5-HT levels. The present study extends these previous findings by examining a longer time course of MCAT-induced DA and 5-HT effects and using an i.p.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These results are consistent with previous microdialysis studies in both rats (Baumann et al, 2000;Kehr et al, 2011) and nonhuman primates (Laruelle et al, 1997;Murnane et al, 2010;Sawyer et al, 2012), and confirm the sensitivity of this microdialysis procedure to changes in NAc DA and 5-HT levels produced by agents that have been extensively evaluated. Also consistent with a previous MCAT microdialysis study (Cozzi et al, 2013), MCAT displayed a greater potency to increase NAc DA versus 5-HT levels. The present study extends these previous findings by examining a longer time course of MCAT-induced DA and 5-HT effects and using an i.p.…”
Section: Discussionsupporting
confidence: 77%
“…Like methamphetamine, MCAT functions as a monoamine transporter substrate that selectively promotes release of dopamine (DA) and norepinephrine over serotonin (5-HT) (Cozzi et al, 1999(Cozzi et al, , 2013Baumann et al, 2012). Consistent with MCAT's Schedule I controlled substance classification in the United States, MCAT increases striatal and nucleus accumbens (NAc) DA levels as measured by in vivo microdialysis in rats (Gygi et al, 1997;Cozzi et al, 2013). Furthermore, MCAT functions as a reinforcer in nonhuman primate drug self-administration procedures (Kaminski and Griffiths, 1994) and produces an abuse-related facilitation of intracranial self-stimulation (ICSS) in rats .…”
Section: Introductionmentioning
confidence: 99%
“…Further uptake inhibition assays in rat brain synaptosomes employing MDPV analogs confirmed that the α-alkyl chain is essential for hDAT affinity, whereas the methylenedioxy group does not affect affinity (101). Substituting a trifluoromethyl on the 3 or 4 position of MCAT’s ring increases the compound’s selectivity towards SERT over NET and DAT (102). Second generation MEPH analogs also elicit release through SERT and DAT (5).…”
Section: Mechanism Of Action Of Synthetic Cathinonesmentioning
confidence: 99%
“…Thus, the carbon atoms 3 and 5 exchange their numbering on going from tautomer a to b. There is ample information in the literature that a trifluoromethyl group is an interesting pharmacophore [26,27,28] even in pyrazole derivatives [29,30,31] including the well-known anti-inflammatory Celecoxib [32]. 19 F, nitromethane and CFCl 3 respectively.…”
Section: Introductionmentioning
confidence: 99%